Inspirasi Bunga Anemone Sebagai Sumber Ide Penciptaan Modest Fashion Pria dan Wanita - Shaumu, Elma Madani; Yulistiana, Yulistiana (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
Anemone flowers are ornamental plants, they have several beautiful colors, one of which is burgundy. The purpose of writing this article is to describe the manufacturing process and finished results in creating modest fashion and men’s clothing using the idea of ​​Anemone flowers. The method used in this writing is the Double Diamond Design Process consisting of the stages: discover, define, develop and deliver. The initial stage of discover, design which includes searching for inspiration. The second stage, define, creates a moodboard after determining the source of the idea. Develop stage, making the development of five basic designs for modest fashion and men’s clothing. The final stage of delivery, the stage of applying details and decorations, is in modest fashion, applying the A silhouette, embroidery details and tucking inspired by the wave shape of anemone flowers. Details on men’s clothing, applying asymmetrical shapes to. The detailed application of the Palembang songket cloth refers to the borderless theme, namely a combination of east and west styles. The results are modest fashion and men’s clothing as expected, having a smart and casual style with an elegant look and a center of interest that is realized in the clothing details.